Are Assessment Exemplars Perceived to Support Self-Regulated Learning in Teacher Education? - Grainger, Peter R.; Heck, Deborah; Carey, Michael D. (Frontiers in Education, 2018)
Assessment exemplars are a tool to guide students to what is valued by assessors in a specific assessment task, in short, as examples which illustrate, typically, dimensions of quality. Often high quality exemplars are provided. We were interested in researching the perceived efficacy and impact of a variety of assessment exemplars, ranging from low to high quality, in teacher education courses at a regional university. We surveyed 72 students and found that students accessed exemplars regularly and found them useful in providing detailed guidance that went beyond the descriptions of assessment tasks found in course outlines and assessment rubrics. They valued various types of exemplars, a range of quality, and the inclusion of annotated and un-annotated versions of exemplars.